The Implementation Of Good Corporate Governance On Banking Industry In Indonesia: Bibliometric Analysis Of GCG - Firman Billy Fanandi; Nurul Asfiah (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This study is to investigate the implementation of Good Corporate Governance (GCG) in the Indonesian banking industry through a bibliometric approach. Through bibliometric analysis, this study explores trends, patterns and research focus related to GCG in the Indonesian banking context. This research utilizes bibliographic data from various academic and professional sources relevant to the topic. Bibliometric methods are used to analyse the number of publications, related journals, the most productive authors, and the keywords most commonly used in literature related to GCG in the Indonesian banking sector. The results of the analysis prove that the implementation of good corporate Governance in banking in Indonesia is not running optimally. There are several factors which encourages good corporate governance not to be implemented in banking in Indonesia maximally, such as implementing transparency, accountability, responsibility, fairness and independence are not fully implemented in banking in Indonesia. The implications of these findings can provide guidance for practitioners, regulators and researchers to improve GCG practices and strengthen the stability and sustainability of the banking industry in Indonesia.